Bioavailability and soil-to-crop transfer of heavy metals in farmland soils: A case study in the Pearl River Delta, South China. (April 2018) - Zhang, Jingru; Li, Huizhen; Zhou, Yongzhang; Dou, Lei; Cai, Limei; Mo, Liping; You, Jing
Abstract: Soil-bound heavy metals are of great concern for human health due to the potential exposure via food chain transfer. In the present study, the occurrence, the bioavailability and the soil-to-crop transfer of heavy metals in farmland soils were investigated based on data from two agricultural areas, i.e. Sihui and Shunde in South China. Six heavy metals (As, Cu, Hg, Mn, Ni and Pb) were quantified in the farmland soils. The mean single pollution level indices ( PI ) were all lower than 1 except for Hg in soils from Shunde ( PI = 1.51 ± 0.46), suggesting the farmland soils were within clean and slightly polluted by heavy metals. As, Cu, Ni and Pb were found to be mostly present in the non-bioavailable form. The majority of Hg was considered potentially bioavailable, and Mn was found to be largely bioavailable. Soil pH was an important factor influencing bioavailability of soil-bound heavy metals. The concentrations of heavy metals in vegetables from Sihui and Shunde were within the food hygiene standards, while the rice grain from Sihui was polluted by Pb ( PI = 10.3 ± 23.4). Total soil concentrations of heavy metals were not correlated to their corresponding crop concentrations, instead, significant correlations were observed for bioavailable concentrations in soil. The results supported the notion that the bioavailability of the investigated heavy metals in the soil was largely responsible for their crop uptake. The soil-to-crop transfer factors based on bioavailable concentrations suggested that Cu, As and Hg in soils of the study area had greater tendency to be accumulated in the vegetables than other heavy metals, calling for further human health assessment by consuming the contaminated crops. Graphical abstract: Image 1 Highlights: The farmland soil was slightly polluted by Hg in the studied area in South China. Soil pH was a key factor influencing bioavailability of soil-bound metals. Rice grain from Sihui was heavily polluted by Pb. Bioavailable fraction of heavy metals better predicted their crop concentrations. Cu, As and Hg were accumulated more in vegetables than other metals. Abstract : Bioavailability-based soil-to-crop transfer factors suggested that Cu, As and Hg in farmland soils from South China had higher tendency to be accumulated in the vegetables than other heavy metals.